(untitled) (Conference Zone, 2022)
Article based on creating a personality-oriented educational environment in the preschool educational institution, which allows creating conditions for full-fledged physical, spiritual, psychoemotional health, interpersonal, group developmental interaction of children, parents, teachers and specialists. Tasks are educating the social and personal qualities of preschoolers who can think in an extraordinary and creative way; develop initiative, curiosity, arbitrariness, the ability for creative selfexpression, stimulate communicative, cognitive, game and other activity of children in various activities; to teach children to apply modern innovative technologies aimed at successful socialization of the individual in society and increasing the level of intellectual thinking and creative imagination